(untitled) (Research, Society and Development, 2023)
Purpose: to verify the influence of high-frequency audiometry (HFA), an audiological test not included in conventional audiology diagnoses, but of great importance in the early detection of hearing loss, in the diagnosis and/or characterization of tinnitus. As well as the relationship of tinnitus in the proposal of audiological evaluation with HFA. Methods: a bibliographic search was carried out in six national scientific journals of speech therapy/audiology and otorhinolaryngology, with a wide range of indexes. Results: from the literature search, 119 references were identified; and from these, 66 abstracts were examined. At the end of the verification of the articles, only three studies were chosen within the inclusion criteria. The samples included subjects complaining of tinnitus and normal hearing, temporomandibular disorders and possible sudden hearing loss. It was possible to observe that the methodology of the studies contemplated the evaluation of the HFA and other complements, such as otoacoustic emissions, acuphenometry, auditory processing behavioral evaluation and tinnitus questionnaires. It was not possible to identify in the studies the use of an AAF structured protocol, including one that referenced some standard normality. Conclusion: Despite the few publications in these journals related to the use of HFA associated with tinnitus, the studies presented samples of patients with tinnitus that do justice to the plurality of this symptom, as well as the diversity of auditory assessment aimed at patients with tinnitus and normal hearing.